1987
DOI: 10.1128/jcm.25.12.2274-2277.1987
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and clinical evaluation of isolation media for Campylobacter jejuni

Abstract: Six selective isolation media were evaluated for their ability to support the growth of Campylobacterjejuni. Colony counts of 70 isolated strains of C. jejuni and recovery studies on these strains in simulated positive feces samples demonstrated that Bolton and Hutchinson' charcoal, cefoperazone, deoxycholate agar and Karmali's charcoal-based selective medium produced the highest recovery rates with the greatest suppression of other fecal flora. C. jejuni colonies were more easily recognized on charcoal-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 12 publications
2
15
0
1
Order By: Relevance
“…Traditionally, mCCDA medium has been widely used for the recovery of campylobacters (Hutchinson and Bolton, 1984;Gun-Munro et al, 1987). Plating onto CAT agar (Aspinall et al, 1993) has since been shown to be superior to mCCDA agar and more sensitive for isolation of a wider variety of Campylobacter spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, mCCDA medium has been widely used for the recovery of campylobacters (Hutchinson and Bolton, 1984;Gun-Munro et al, 1987). Plating onto CAT agar (Aspinall et al, 1993) has since been shown to be superior to mCCDA agar and more sensitive for isolation of a wider variety of Campylobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…The modified charcoal cefoperazone deoxycholate agar (mCCDA) medium has been used traditionally for the recovery of campylobacters (Hutchinson and Bolton, 1984;Gun-Munro et al, 1987). Methods developed subsequently for Campylobacter isolation include a membrane filtration technique and direct plating on basal agar containing cefoperazone, amphotericin and teicoplanin (CAT) selective agents.…”
Section: Introductionmentioning
confidence: 99%
“…Preston agar was less effective than either mCCDA or Karmali with the growth of other competing bacteria making the identification of Campylobacter colonies difficult. Preston agar has a different composition and has been reported as being less selective and less effective for direct isolation of Campylobacter from human faecal samples than mCCDA and Karmali agars (Merino et al 1986;Gun-Munro et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial analysis of samples was by a five-tube MPN method (Donnison 2002); briefly, primary enrichment was in a Exeter broth (Martin et al 1996) with resuscitation for 24 h at 37°C followed by transfer to 42°C for a further 24 h. Primary enrichment was followed by secondary selective plating on modified charcoal cefoperazone agar (mCCDA; Oxoid, Basingstoke, UK) with plates incubated in a microaerophilic atmosphere (CampyGen, Oxoid, UK) for 24 h at 42°C. mCCDA has been demonstrated to recover campylobacter effectively (Gun-Munro et al 1987;Corry et al 1995;Engberg et al 2000). Its selectivity is due to inhibition of nontarget micro-organisms by the antibiotics cefoperazone and amphotericin B, and promotion of campylobacter growth due to inclusion of quenching and detoxifying agents (Bolton et al 1984).…”
Section: Analysis Of Bacteriamentioning
confidence: 99%